VD_FINDINFO Jug / 2012 / 70 vom 25. August 2011 - VD Tribunal cantonal (2011)
APPRÉCIATION DES PREUVES, ORDRE PUBLICEN GÉNÉRAL, OPPOSITION À UN ACTE DE L'AUTORITÉ | 10 al. 2 CPP (CH), 398 al. 4 CPP (CH), 14 al. 3 LVCPP